Компарација на безбедноста и ефикасноста на бесполимерни и полимерни стентови обложени со лек применети при перкутани коронарни интервенции - Трајчески, Тед (Медицински факултет, УКИМ, Скопје, 2018)
Background: Percutaneous coronary interventions (PCI) result in implantation of different kinds of stents. Newest-generation stents aim to optimize polymer compatibility, drug elution, toxicity profiles, and stent design to optimize reendothelialisation with the aim of improving clinical outcomes. The polymer itself has garnered considerable attention because polymer-induced inflammation can lead to positive remodelling and impaired arterial healing and re-endothelialisation. Therefore, new stents without polymer carrier, or biodegradable polymers have been invented. The aim of this study was to compare the late effects and the safety of polymer-free and polymer-based stents in a non-inferiority analysis. Methods: The study was a mono-centric longitudinal and prospective study. We included 194 patients with significant coronary stenosis, and need of stent intervention. Patients were assigned to one of the two groups according to randomization to Polymer Free Stent (PFS) or Polymer Bearing Stent (PBS). Groups were matched for sex, age and cardiovascular risk factors. In one patient, no matter the number of lesions and vessels, stents of one group was assigned. Patients were followed for 9 month and primary endpoint composite score - Major Adverse Cardiac Events (MACE), and stent thrombosis were notified. Results: There was no difference in the incidence of the composite score MACE in 9 months in the two groups of stents (9.3% vs. 6.2%, p>0.05). Definitive late stent thrombosis was not statistically different in the both group of stents. As for the whole group, bleeding risk was low, Angina Pectoris and heart failure did not advance through 9 months of follow up. Conclusion: There were no significant differences in clinical outcome between polymer-free and polymer-based stents in the nine months follow-up period. Differences in stent designs allow individualized approach in the treatment. There is no universal stent, but assessment is needed for every treated patient and lesion.
Comparative study on safety and efficacy of polymer bearing stents versus polymer free stents in percuteneous coronary interventions
Докторска дисертација одбранета во 2018 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Драган Даниловски.
Keywords: coronary stenosis, percutaneous coronary interventions, polymers, stents